Serum IL-6, IL-1β, IL-8, and Cerebrospinal Fluid Biochemical Profiles in Patients with Lateral Skull Base Temporal Bone Fractures and Cerebrospinal Fluid Leak: Serum IL-6, IL-1β, IL-8 Cerebrospinal Fluid Biochemical - Zhu, Jianhua; Qian, Juhua (Journal of Medical Biochemistry, 2025)
Aim: This study evaluates the impact of cranial reconstruction therapy combined with lumbar drainage on inflammatory cytokine levels (IL-6, IL-1β, IL-8), serum albumin, and cerebrospinal fluid biochemical markers in patients with lateral skull base temporal bone fractures and cerebrospinal fluid leakage. Additionally, the role of nutritional and psychological care in patient recovery is assessed.Methods: A total of 130 patients with temporal bone fractures and CSF leakage who underwent craniotomy repair surgery between May 2022 and May 2024 were enrolled. Patients were randomly assigned to either a control group (CG), receiving craniotomy and standard nutritional care, or an observation group (OG), receiving cranial reconstruction combined with lumbar drainage and nutritional intervention. CSF protein, glucose, and chloride levels were measured on postoperative day 7. Systemic inflammatory response was assessed by measuring temperature, WBC count, CRP, IL-6, IL-1β, and IL-8 at 7 and 15 days postoperatively. Nutritional status was evaluated using ALB, TP levels, and SGA scores before and after treatment.Results: By postoperative day 7, OG patients exhibited lower CSF protein levels and higher glucose and chloride levels compared to CG (P < 0.05), with all values remaining within the normal range. Inflammation markers (IL-6, IL-1β, IL-8, WBC, and CRP) were significantly lower in OG compared to CG at day 7 (P < 0.05), with further reduction by day 15 (P < 0.01), suggesting faster resolution of inflammation in OG. Serum albumin levels were significantly higher in OG postoperatively (P < 0.01), indicating better nutritional recovery. No significant difference was observed between groups for TP and SGA scores.Conclusion: Cranial reconstruction therapy combined with lumbar drainage accelerates the resolution of inflammation (IL-6, IL-1β, IL-8), improves cerebrospinal fluid biochemical markers, and enhances nutritional recovery (albumin levels), leading to better clinical outcomes. The inclusion of nutritional and psychological support further enhances patient recovery and quality of life. These findings highlight the importance of monitoring inflammatory and nutritional biomarkers to optimize postoperative management in temporal bone fractures with CSF leakage.
Keywords: IL-6, IL-1β, IL-8,Nutritional care; lateral skull base temporal bone fractures; cerebrospinal leakage; cranial reconstructive therapy; lumbar big-pool drainage; clinical outcome